1995
DOI: 10.1016/0092-8674(95)90337-2
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in sister chromatid separation are needed for b-type cyclin proteolysis in budding yeast

Abstract: B-type cyclin destruction is necessary for exit from mitosis and the initiation of a new cell cycle. Through the isolation of mutants, we have identified three essential yeast genes, CDC16, CDC23, and CSE1, which are required for proteolysis of the B-type cyclin CLB2 but not of other unstable proteins. cdc23-1 mutants are defective in both entering and exiting anaphase. Their failure to exit anaphase can be explained by defective cyclin proteolysis. CDC23 is required at the metaphase/anaphase transition to sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
504
1
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(521 citation statements)
references
References 40 publications
14
504
1
2
Order By: Relevance
“…These consequences could be explained by at least two mechanisms. The first is that Cdc2Op is important for the anaphase-promoting complex (APC), a recently discovered protein assembly that is thought to play an important role in the ubiquination of cyclins and other proteins whose degradation is important for the metaphase to anaphase transition in mammalian cells , Xenopus (King et al, 1995), and S. cerevisiae (Irniger et al, 1995). The second explanation is that there is a regulatory checkpoint that is dependent on the dynamic activity of spindle MTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These consequences could be explained by at least two mechanisms. The first is that Cdc2Op is important for the anaphase-promoting complex (APC), a recently discovered protein assembly that is thought to play an important role in the ubiquination of cyclins and other proteins whose degradation is important for the metaphase to anaphase transition in mammalian cells , Xenopus (King et al, 1995), and S. cerevisiae (Irniger et al, 1995). The second explanation is that there is a regulatory checkpoint that is dependent on the dynamic activity of spindle MTs.…”
Section: Discussionmentioning
confidence: 99%
“…A fzy mutant fails to degrade cyclins A and B and cells arrest in metaphase, suggesting that cell cycle-regulated cyclin proteolysis is dependent on the fzy' gene. Recent studies have shown that the exit from mitosis (Holloway et al, 1993;Surana et al, 1993), as well as sister chromatid separation (Irniger et al, 1995), is dependent on ubiquitin-dependent proteolysis. Thus, the increase in spindle MTs observed in fzy mutants may be explained by a failure to degrade protein(s) necessary for anaphase onset (Dawson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This also might be due to the defect of cyclin degradation. Even the mitotic B-cyclin can induce DNA replication (Amon et al, 1994;Irniger et al, 1995;Fisher and Nurse, 1996); therefore, these cyclins escaping from degradation would be responsible for the promotion of the progression from G 1 to S-phase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a classical E3 such as Ubr1, and the HECT domaincontaining proteins (Huibregtse et al 1995;Varshavsky 1996), novel E3s have been identified as crucial regulatory factors for cell cycle progression. These include the APC/cyclosome (the Anaphase Promoting Complex, Hershko et al 1994;Irniger et al 1995;King et al 1995;Sudakin et al 1995) and the SCF complex (Skp1-Cullin-1/Cdc53-F-box, Feldman et al 1997;Skowyra et al 1997).…”
Section: Introductionmentioning
confidence: 99%